2015
DOI: 10.1590/1806-9282.61.05.474
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations in breast and serous ovarian cancer young patients: a systematic review and meta-analysis

Abstract: Objective: our aim was to evaluate whether somatic mutations in five genes were associated with an early age at presentation of breast cancer (BC) or serous ovarian cancer (SOC). Methods: COSMIC database was searched for the five most frequent somatic mutations in BC and SOC. A systematic review of PubMed was performed. Young age for BC and SOC patients was set at ≤35 and ≤40 years, respectively. Age groups were also classified in <30years and every 10 years thereafter. Results: twenty six (1,980 patients, 111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 75 publications
2
20
0
1
Order By: Relevance
“…In BC, the most frequently mutated genes are PIK3CA (25%), TP53 (23%), CDH1 (11%), GATA3 (7%), and PTEN (5%) 54,55 . In YWBC, Encinas et al 56 performed a systematic review to analyze whether somatic mutations in five genes were associated with an early age at presentation of BC. They found a higher frequency of wild-type PIK3CA associated with early-onset BC, although not statistically significant when employing a multivariate model.…”
Section: Somatic Mutation Profile In Ywbcmentioning
confidence: 99%
See 1 more Smart Citation
“…In BC, the most frequently mutated genes are PIK3CA (25%), TP53 (23%), CDH1 (11%), GATA3 (7%), and PTEN (5%) 54,55 . In YWBC, Encinas et al 56 performed a systematic review to analyze whether somatic mutations in five genes were associated with an early age at presentation of BC. They found a higher frequency of wild-type PIK3CA associated with early-onset BC, although not statistically significant when employing a multivariate model.…”
Section: Somatic Mutation Profile In Ywbcmentioning
confidence: 99%
“…They found a higher frequency of wild-type PIK3CA associated with early-onset BC, although not statistically significant when employing a multivariate model. Moreover, TP53 was mutated in 20% of tumors from both younger and older patients 56 . Azim et al 29 examined the genomic aberrations of tumors from three different age groups, ≤45 (125 patients), 46-69 (486 patients), and ≥70 (169 patients) years of age.…”
Section: Somatic Mutation Profile In Ywbcmentioning
confidence: 99%
“…Mutations in Ras, PI3 K/AKT, and mammalian target of rapamycin pathways can lead to unrestricted tumor cell growth [30]. Encinas G et al and his colleagues reported a somatic mutation in tyrosine kinases, which can constitutively activate the PI3 K/AKT pathway in breast cancer leading to increased productivity of the mammalian target of rapamycin pathway, revealing that targeted therapies with mammalian target of rapamycin inhibitors could be considered in such cases [31]. Our study reports a 33 % PIK3CA mutation rate in small cell carcinoma of the breast, which could lead to the consideration of the use of mammalian target of rapamycin inhibitors as a potential therapeutic agent in small cell carcinoma of the breast, but further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…17 Our results have potential clinical utility, as low expression of ALDH5A1 was associated with a worse OS inTP53 mutation-type SOC patients. Thus, the significance of the correlation between p53 and individual ALDH5A1 in OC should be further analyzed.…”
Section: Discussionmentioning
confidence: 64%